The Ecuadorian Paralympic tennis: an approach to the real historical context of its sport evolution/El tenis paralímpico ecuatoriano: un acercamiento al contexto histórico real de su evolución deportiva - Roberto Manolo Castro Cevallos (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
The Paralympic tennis at international level has had a remarkable development in the last decades, so many ethnographic studies have been made since its creation. The objective of this research is the historical collection of informative data about the origin of Paralympic tennis in Ecuador, with a description of the characters who made such events possible, the circumstances and their influence on the future of the sport. The study was framed in the qualitative paradigm, from a complex historical field, applying the ethnographic method to structure the theoretical information collected through the techniques of documentary review, supported by a category matrix instrument and the interview with two question bank instruments. The first one applied to five personalities of the Ecuadorian Paralympic tennis among sports leaders and coaches, approaching the historical dimension of the Ecuadorian Paralympic tennis; the second one applied to five elite sportsmen of wheelchair tennis with the dimension of sports anecdotes in the Paralympic tennis. The data was analyzed through the technological tool Atlas.ti, emerging unpublished and relevant findings, with an approach to the real historical context. This study will create a structural basis with which athletes, coaches, managers and sports researchers will understand the historical process and evolutionary development that this sport has had, ensuring a sense of relevance that, added to the strong motivation and difficulties overcome, will allow the acquisition of tools necessary for personal improvement and sports against their disabilities.